Pengaruh Pengangguran, Belanja Modal dan Belanja Bantuan Sosial terhadap Kemiskinan di Kota Banjarbaru Tahun 2010-2020 - Mellenia Medina, Salma; Nur, Muhammad Anshar (PPJP ULM, 2024)
This study was conducted to (1) analyze the effect of Unemlployment, Caapital Expeenditure and Social Assistance Expenditure simultaneously on Poverty in Banjarbaru City in 2010-2020; (2) analyze the effect of unemployment, capital expenditure and partial in Banjarbaru City in 2010-2020. Descriptive quantitative and using multiple linear regression analysis techniques with time series and using Eviews 10 software is a type of this research. This study provides results that show that independently, namely Unemployment, Capital Expenditure and Social Assistance Expenditure have a significant effect on Poverty in Banjarbaru City 2010-2020. Only the variable of Unemployment has a significant effect on Poverty in Banjarbaru City in 2010-2020.